Microbiota dysbiosis impact on the metabolism of T3 and T4 hormones and its association with thyroid cancer - Cadena-Ullauri, Santiago; Guevara-Ramírez, Patricia; Paz-Cruz, Elius; Ruiz-Pozo, Viviana A.; Tamayo-Trujillo, Rafael; Zambrano, Ana Karina (Frontiers in Cell and Developmental Biology, 2025)
This review explores the impact of gut microbiota dysbiosis on thyroid hormone metabolism and its potential association with thyroid cancer. The analysis highlights specific bacterial genera linked to thyroid dysfunction, the role of gut microbiota in iodine absorption, and mechanisms connecting dysbiosis with thyroid disorders such as hypothyroidism, hyperthyroidism, Hashimoto’s thyroiditis, and Graves’ disease. Additionally, it examines the potential of gut microbiota as a biomarker for diagnosis and personalized treatment, as well as the prospect of probiotics and microbiota-targeted treatments. The review emphasizes the importance of conducting additional research to fully understand microbiota-thyroid interactions and develop appropriate therapies to improve clinical outcomes and patient quality of life.